Comparative studies on the fish-killing activities of Chattonella marina isolated in 1985 and Chattonella antiqua isolated in 2010, and their possible toxic factors. Issue 4 (2nd April 2016) - Cho, Kichul; Sakamoto, Jun; Noda, Tatsuki; Nishiguchi, Tomoki; Ueno, Mikinori; Yamasaki, Yasuhiro; Yagi, Motoaki; Kim, Daekyung; Oda, Tatsuya
Abstract: Chattonella antiqua isolated in 2010 showed extremely more potent fish-killing activities against red sea bream, Japanese horse mackerel, and blue damselfish than those of Chattonella marina isolated in 1985. Chemiluminescence and electron spin resonance (ESR) analyses suggested greater reactive oxygen species (ROS)-producing activity of C. antiqua than that of C. marina . Sodium benzoate, a hydroxyl radical scavenger, significantly suppressed the fish-killing activity of C. antiqua on blue damselfish. The chlorophyll level in the gill tissue of blue damselfish exposed to flagellate cells increased along with the exposure time, and the cell count of gill-associated C. antiqua estimated with chlorophyll level was higher than that of C. marina . These results suggest that the ROS-producing activity and affinity of Chattonella cells to the gill surface may be important factors influencing the fish-killing activity of Chattonella species. Graphical abstract: : ROS-mediated gill tissue damage by C. antiqua may lead to fish death